2020
DOI: 10.3390/ijerph17030923
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Related Factors of Intention to Perpetrate Dating Violence among University Students Using the Theory of Planned Behavior

Abstract: Dating violence (DV) is a major public health problem among youth. The majority of DV studies in Taiwan involve the assessment of DV without the use of a robust psychological framework to guide research accuracy. Therefore, the purpose of this study was to utilize the Theory of Planned Behavior (TPB) to assess intention and other salient factors related to DV among university students. A two-phase, mixed-method design study was conducted among university students from seven universities in Taiwan, aged 18 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 50 publications
2
20
2
Order By: Relevance
“…Cronbach's α and McDonald's ω were then applied to the confirmed structure of the WHOQOL-AGE to understand its internal consistency. A Cronbach's α > 0.7 and a McDonald's ω > 0.7 were considered as acceptable ( 26 , 27 ). Moreover, known-group validity was tested to understand whether the WHOQOL-AGE could effectively distinguish the different levels of QoL between older people living in the community and those living in an institution.…”
Section: Methodsmentioning
confidence: 99%
“…Cronbach's α and McDonald's ω were then applied to the confirmed structure of the WHOQOL-AGE to understand its internal consistency. A Cronbach's α > 0.7 and a McDonald's ω > 0.7 were considered as acceptable ( 26 , 27 ). Moreover, known-group validity was tested to understand whether the WHOQOL-AGE could effectively distinguish the different levels of QoL between older people living in the community and those living in an institution.…”
Section: Methodsmentioning
confidence: 99%
“…Meta‐analytic research has provided support for the HAPA constructs of planning and self‐efficacy in predicting health behaviours (Zhang et al, 2019). Previous research has also shown intention, planning, and self‐efficacy to predict health preventive behaviours more specifically (Caudwell, Keech, Hamilton, Mullan, & Hagger, 2019; Cheng et al ., 2019; Fung et al ., 2019; Hamilton, Kirkpatrick, Rebar, & Hagger, 2017; Hou, Lin, Wang, Tseng, & Shu, 2020; Lin, Scheerma, Yaseri, Pakpour, & Webb, 2017; Lin et al ., 2018, 2020; Lin, Updegraff, & Pakpour, 2016; Reyes Fernández, Knoll, Hamilton, & Schwarzer, 2016; Strong et al ., 2018; Zhang et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Interventions can then be designed to target and change these beliefs or the value placed on them, thereby affecting attitude, subjective norm, or perceived behavioral control, leading to changes in intentions and behaviors [8,9]. The TPB has also been used successfully to predict and explain a wide range of health behaviors including exercise, smoking and drug use, HIV prevention behaviors, among others [8][9][10][11][12][13][14][15][16]. Models of behavior, such as the TPB provide a conceptual framework that allows program designers and policy makers to detect the fundamental features that determine behavior and thus design valuable interventions.…”
Section: Introductionmentioning
confidence: 99%